2009
DOI: 10.1073/pnas.0900196106
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of chemokine receptor by Toll-like receptor 2 is critical to neutrophil migration and resistance to polymicrobial sepsis

Abstract: Patients with sepsis have a marked defect in neutrophil migration. Here we identify a key role of Toll-like receptor 2 (TLR2) in the regulation of neutrophil migration and resistance during polymicrobial sepsis. We found that the expression of the chemokine receptor CXCR2 was dramatically down-regulated in circulating neutrophils from WT mice with severe sepsis, which correlates with reduced chemotaxis to CXCL2 in vitro and impaired migration into an infectious focus in vivo. TLR2 deficiency prevented the down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
238
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(260 citation statements)
references
References 32 publications
(34 reference statements)
15
238
0
3
Order By: Relevance
“…Similarly, expression of TLR2, which has been previously demonstrated to regulate neutrophil migration via CXCR2, and surface expression of CXCR2 did not differ between WT and GILZ-KO neutrophils and was not affected by DEX treatment (Fig. 2C) (32).…”
Section: Effect Of Dex On Neutrophil Migration In Gilz-ko Mice With Pmentioning
confidence: 85%
“…Similarly, expression of TLR2, which has been previously demonstrated to regulate neutrophil migration via CXCR2, and surface expression of CXCR2 did not differ between WT and GILZ-KO neutrophils and was not affected by DEX treatment (Fig. 2C) (32).…”
Section: Effect Of Dex On Neutrophil Migration In Gilz-ko Mice With Pmentioning
confidence: 85%
“…Paradoxically, LTA has also been shown to be anti-inflammatory in suppressing neutrophil recruitment in response to polymicrobial sepsis through the downregulation of the chemokine receptor CXCR2 on neutrophils [16]. TLR2 À/À animals showed decreased cytokine production, higher bacterial clearance and improved survival.…”
Section: Introductionmentioning
confidence: 99%
“…LTA-induced Weibel-Palade body exocytosis in aortic endothelial cells with release of von Willebrand factor and P-selectin was also enhanced by IFN-g priming [15]. Priming has been attributed to enhanced TLR2 expression [12] or the recruitment of intracellular TLR2 to the cell membrane [13].Paradoxically, LTA has also been shown to be anti-inflammatory in suppressing neutrophil recruitment in response to polymicrobial sepsis through the downregulation of the chemokine receptor CXCR2 on neutrophils [16]. TLR2 À/À animals showed decreased cytokine production, higher bacterial clearance and improved survival.…”
mentioning
confidence: 99%
“…They play a crucial role in modulating innate immune-inflammatory response and outcome of sepsis. Disruption or antibody neutralization of specific TLRs including TLR2, TLR3, TLR4, and TLR9 has been shown to improve survival in a polymicrobial mice model of sepsis (6)(7)(8). Further, a recent study has reported cross-talk between TLR4 and TLR2 signaling pathways in augmenting proinflammatory response and mortality in sepsis (9).…”
mentioning
confidence: 99%